Mycorrhizal Interventions for Sustainable Potato Production in Africa - Chifetete, Varaidzo W.; Dames, Joanna F. (Frontiers in Sustainable Food Systems, 2020)
The potato (Solanum tuberosum L.) is an important tuber crop with high dietary value that could potentially help to alleviate malnutrition and hunger in Africa. However, production is expensive, with high fertilizer and pesticide demands that lead to environmental pollution, and tillage practices that negatively affect soil structure. Microorganisms of different types have increasingly been found to be useful as biofertilizers, and arbuscular mycorrhizal (AM) fungi are an important crop symbiont. AM fungi have been shown to increase tolerance of crop plants to drought, salinity and disease by facilitating water and nutrient acquisition and by improving overall soil structure. However, the establishment and maintenance of the symbioses are greatly affected by agricultural practices. Here, we review the benefits that AM fungi confer in potato production, discuss the role and importance of mycorrhiza helper bacteria, and focus on how AM fungal diversity and abundance can be affected by conventional agricultural practices, such as those used in potato production. We suggest approaches for maintaining AM fungal abundance in potato production by highlighting the potential of conservation tillage practices augmented with cover crops and crop rotations. An approach that balances weed control, nutrient provision and AM fungal helper bacterial populations, whilst promoting functional AM fungal populations for varying potato genotypes, will stimulate efficient mycorrhizal interventions.